2021
DOI: 10.3389/fimmu.2021.688643
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CLEC-2 and Its Ligands in Thromboinflammation

Abstract: C-type lectin-like receptor 2 (CLEC-2, also known as CLEC-1b) is expressed on platelets, Kupffer cells and other immune cells, and binds to various ligands including the mucin-like protein podoplanin (PDPN). The role of CLEC-2 in infection and immunity has become increasingly evident in recent years. CLEC-2 is involved in platelet activation, tumor cell metastasis, separation of blood/lymphatic vessels, and cerebrovascular patterning during embryonic development. In this review, we have discussed the role of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 99 publications
0
34
0
Order By: Relevance
“…CLEC1b (CLEC-2) is a C-type lectin-like receptor 2 that is expressed on B lymphocytes, granulocytes, monocytes, and dendritic cells, as well as Kupffer cells and platelets, and binds to various ligands including the mucin-like protein podoplanin (PDPN) [ 53 ]. It was found that LPS and other inducers of inflammation can increase the expression of CLEC-2, but this is not typical for all macrophage subpopulations [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CLEC1b (CLEC-2) is a C-type lectin-like receptor 2 that is expressed on B lymphocytes, granulocytes, monocytes, and dendritic cells, as well as Kupffer cells and platelets, and binds to various ligands including the mucin-like protein podoplanin (PDPN) [ 53 ]. It was found that LPS and other inducers of inflammation can increase the expression of CLEC-2, but this is not typical for all macrophage subpopulations [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that LPS and other inducers of inflammation can increase the expression of CLEC-2, but this is not typical for all macrophage subpopulations [ 54 ]. According to some data, CLEC-2 in Kupffer cells is detected at a low level [ 53 ], while it can participate in the secretion of proinflammatory cytokines [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…C-type lectin-like receptor 2 (CLEC-2), which is a platelet receptor, binds to PDPN and plays a critical role in PDPN-mediated platelet aggregation and lung metastases [15][16][17]. CLEC-2 was first discovered as a platelet receptor for snake venom, rhodocytin, known as a platelet aggregation-inducing toxin [18][19][20].…”
Section: Molecular Functions Of Pdpn Extracellular Domainmentioning
confidence: 99%
“…CLEC-2 and its ligands serve as a molecular link between platelets, immune cells, and target cells, as well as a unique mechanism for thrombosis. As a result, CLEC-2-related pathways could be used to treat thromboinflammation [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers discovered that podoplanin was upregulated in the venous wall while trying to figure out the mechanism of cancer-mediated inflammation. CLEC-2 may thus have a role in tumour-induced thromboinflammation, and persistent long-term exposure to inflammatory cytokines causes thrombosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%